(untitled) (Applied Biological Research, 2024)
The wide application of fungicides in agriculture and human medicines have raised environmental concerns and potential impact on aquatic ecosystem. Tebuconazole is a broad-spectrum fungicide used as curative and protective against several fungal pathogens. However, owing to its environmental persistence, it can have long term adverse effects. The present study was aimed to assess the toxic effects of tebuconazole on the digestive system of fish carp Cyprinus carpio. The fish were exposed to 6.47 and 8.09 µL L-1 concentrations of tebuconazole for 30 days. Biochemical parameters viz., lipid peroxidation, protein content, glutathione-s-transferase and phosphatases were determined in the liver and intestine of carp on exposure to tebuconazole. Histopathological analysis was also performed. Reduction in protein and glutathione-s-transferase was observed in time- and dose-dependent manner which may cause rise in lipid peroxides and oxidative stress. Acid and alkaline phosphatase showed elevated activity during the entire exposure time. Significant alterations in the histology of hepatic and intestinal tissues were observed including nuclear alteration, vacuolation and cytoplasmic degeneration in hepatocytes and mucosal alterations in intestine. The result revealed that tebuconazole not only altered the enzymatic activity but also caused oxidative stress and cellular damage. The results confirm the severe damage to fish organs due to tebuconazole, thereby revealing potential impact on aquatic environment.